Development of Google Sites Web Learning Media Integrated Problem Based Learning Model on Hydrocarbon Material - Tira Kania Pardosi; Haqqi Annazili Nasution; Freddy Tua Musa Panggabean (Universitas Negeri Medan, 2026)
This research aims to develop a Google Sites–based web learning media integrated with the Problem Based Learning (PBL) model on hydrocarbon material for senior high school students. The research was conducted at SMA Negeri 2 Percut Sei Tuan using a Research and Development (R&D) approach with the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. The subjects of the study were 34 students of class XI-E. Data were collected through interviews, validation questionnaires, learning outcome tests (pretest and posttest), and teacher and student response questionnaires. The feasibility of the developed media was assessed by material and media experts based on BSNP standards. The results showed that the Google Sites web learning media integrated with the PBL model was categorized as very feasible, with an average validation score of 3.58 for material aspects and 3.51 for media aspects. The effectiveness of the media was indicated by a significant improvement in students’ learning outcomes, with the average pretest score increasing from 36.76 to a posttest score of 87.20 and an N-gain value of 0.79, which falls into the high category. Furthermore, teacher and student responses toward the developed media were very positive, indicating high interest, clarity of material, and ease of use. These findings suggest that Google Sites web learning media integrated with the PBL model is effective in improving students’ understanding and learning outcomes in hydrocarbon material and can be used as an innovative alternative learning media in chemistry instruction.